Inclined magnetic field on second grade nanofluid flow from an inclined stretching sheet with nonlinear mixed convection - Syazwani, Mohd Zokri; Nur Syamilah, Arifin; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh (Akademi Sains Malaysia, 2019)
Present investigation aims to probe into the problem of nonlinear mixed convection flow of second grade nanofluid flow due to an inclined stretching sheet. The simultaneous impacts of inclined magnetic field of acute angle and convective boundary conditions are taken into deliberation. The system of highly nonlinear partial differential equations is transformed into non-linear ordinary differential equations with the aid of similarity transformation variables. The solutions are generated numerically via the Runge-Kutta-Fehlberg Method (RKF 45) and then presented in the form of graph. Obtained results are first authenticated by way of comparison with the documented results of previous publications. Finding reveals that the inclined angle together with magnetic parameter have decelerated the fluid flow. Besides, escalating both Brownian motion and thermophoresis diffusion parameters have enhanced the temperature. In contrast, the concentration profile has reduced owing to incremented Lewis number.